2018
DOI: 10.1021/acssynbio.8b00218
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Electron Transfer by Shewanella oneidensis Controls Palladium Nanoparticle Phenotype

Abstract: Biological production of inorganic materials is impeded by relatively few organisms possessing genetic and metabolic linkage to material properties. The physiology of electroactive bacteria is intimately tied to inorganic transformations, which makes genetically tractable and well-studied electrogens, such as Shewanella oneidensis, attractive hosts for material synthesis. Notably, this species is capable of reducing a variety of transition-metal ions into functional nanoparticles, but exact mechanisms of nanop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 57 publications
2
43
0
Order By: Relevance
“…This leads to an increased deposition rates and, in turn, an increased localised turnover rate of the platinum ions by the autocatalytic abilities of the platinum nanoparticles thus leading overall to larger nanoparticles. This supports previous work which concluded that the NiFe hydrogenase is required for nanoparticle synthesis in Desulfovibrio (18) and also their deposition on the outer membranes in Shewanella (20). Samples of nanoparticles produced by Desulfovibrio transformed with either pMO-2137 or the empty vctor control were analysed using EDS (Energy-dispersive spectroscopy).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This leads to an increased deposition rates and, in turn, an increased localised turnover rate of the platinum ions by the autocatalytic abilities of the platinum nanoparticles thus leading overall to larger nanoparticles. This supports previous work which concluded that the NiFe hydrogenase is required for nanoparticle synthesis in Desulfovibrio (18) and also their deposition on the outer membranes in Shewanella (20). Samples of nanoparticles produced by Desulfovibrio transformed with either pMO-2137 or the empty vctor control were analysed using EDS (Energy-dispersive spectroscopy).…”
Section: Resultssupporting
confidence: 92%
“…The NiFe hydrogenases of D. fructosovorans have been shown to be involved in technetium reduction (17). They similarly have a role, along with a Fe-containing hydrogenase, in Pd(0) deposition and clustering in both the periplasm (18) and on cellular membranes (19), while more recently have been implicated in having a roll in palladium deposition in Shewanella (20). While important for the anaerobic reduction of palladium by Desulfovibrio sp., they are not required for the aerobic reduction of palladium by E. coli (21).…”
Section: Introductionmentioning
confidence: 99%
“…[30] Two key factors of extracellular electron transfer by S. oneidensis, the outer membrane cytochrome, and soluble redox shuttles, that affect Pd nanoparticle formation. [31] It is worth mentioning that the addition of GO significantly increases the recovery rate of Pd in the product. We studied TEM was utilized to visually demonstrate the typical Pd nanoparticles that were decorated on the bacteria cells and rGO sheets in Bio-Pd and Bio-Pd/rGO.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that S. oneidensis MR‐1 has a large number of terminal reductases, which is implicated in electron transfer for the reduction reaction . Two key factors of extracellular electron transfer by S. oneidensis , the outer membrane cytochrome, and soluble redox shuttles, that affect Pd nanoparticle formation …”
Section: Resultsmentioning
confidence: 99%
“…While hybrid cells and materials have been reported that leverage synthetic biology for in situ sensing and chemical synthesis, these studies typically control ET at the transcriptional level, limiting the speed (minutes to hours) at which ET can be regulated for different applications . Overcoming this timescale challenge will enable increased temporal resolution for in situ sensing applications and precision control over ET during chemical and material synthesis . One way to improve the speed at which ET is regulated for these diverse applications is to develop chemical‐induced proteins that control ET through post‐translational mechanisms that operate on faster timescales (seconds to minutes) …”
Section: Introductionmentioning
confidence: 99%